Enterprise Risk Management Implementation Maturity in Non Bank and Financial Companies - Subagio Tjahjono (Faculty of Economic and Business, 2017)
Previous studies of ERM implementation mostly using dummy variable to figure out relation with its determinant. Until today, studies that using risk management maturity as real variable are limited. Therefore, this study intends to determine the maturity level of ERM implementation in non-financial companies listed on Indonesia Stock Exchange during period 2015 and influence of firm’s total assets, total employee, leverage and public ownership to the ERM maturity. The method use are qualitative and multiple regression analysis. The result of data analysis showed that ERM implementation in selected sample during 2015 are still low (majority in initial and repeatable level). In addition, from determinant factors only total asset that have significant influence to the ERM maturity. This result implies that non-financial listed companies are vulnerable to risks. Management should consider future benefit of a mature ERM, not only to comply with regulation.DOI: 10.15408/etk.v16i2.5440